Living with Leprosy: The perception of patients about the stigma of the disease (Research, Society and Development, 2022)
Leprosy is a chronic infectious disease that causes skin lesions and damage to peripheral nerves, which can lead to physical disabilities. Patients carry stigmas and prejudices due to the history and beliefs attributed to the disease, which can cause suffering, affecting self-esteem and impairing their socialization. This study analyzed the presence or absence of stigma related to leprosy from the reports of patients who were in outpatient follow-up and participated in a group for the disease. It also looked at whether participation in the group helped in any way with treatment. Participants: 53 men and women, with a mean age of 55.5 years. Design: exploratory qualitative and quantitative descriptive analysis. Instruments: telephone interviews conducted by two guiding questions: “how does the disease affect your life and how did the host group help you”. Results: 62.3% of the participants reported experiencing prejudice and/or withdrawal from friendships since they received the diagnosis of leprosy. There were reports of decreased self-esteem after sequelae of the disease and withdrawal from acquaintances and family members who were afraid of contagion. The majority (96.2%) of the participants reported that the group helped during the treatment of leprosy. Reception groups in the format of a waiting room in health units can help to improve information and knowledge about leprosy, reducing prejudice and improving the way of dealing with treatment. The lack of information about the disease proves to be a factor that contributed to the maintenance of the stigma that leprosy carries.